Potential antivirulence activity of sub-inhibitory concentrations of ciprofloxacin against Proteus mirabilis isolates: an in-vitro and in-vivo study - Mohamed A. Elhosseini; Tarek E. El-Banna; Fatma I. Sonbol; Maisra M. El-Bouseary (BMC, 2024)
Abstract Background Proteus mirabilis is a significant nosocomial pathogen that is frequently associated with a wide range of infections, necessitating heightened attention to mitigate potential health risks. Hence, this study was performed to investigate the impact of sub-minimum inhibitory concentrations (MICs) of ciprofloxacin (CIP) on Proteus mirabilis clinical isolates. Methods The sub-MICs of CIP were selected using the growth curve approach. The untreated and treated isolates with sub-MICs of CIP were assessed for their biofilm development, motilities on agar, and other virulence factors. The cell morphology of untreated and treated isolates with sub-MIC of CIP was explored using electron microscope. Moreover, the expression levels of the virulence genes in isolates were measured using quantitative real-time PCR. Results Data revealed that sub-MICs of CIP significantly (p < 0.05), in a concentration-dependent manner, inhibited biofilm formation and other virulence factors in the selected isolates. Electron microscope analysis showed cell enlargement and various abnormalities in the cell wall and membrane integrity. Conclusion Sub-MICs of CIP exhibited inhibition of virulence and alterations in morphological integrity against P. mirabilis isolates.